Politicians, Taxes and Debt - YARED, PIERRE (Review of Economic Studies, 2010)
The standard analysis of the efficient management of income taxes and debt assumes a benevolent government and ignores potential distortions arising from rent-seeking politicians. This paper departs from this framework by assuming that a rent-seeking politician chooses policies. If the politician chooses extractive policies, citizens throw him out of power. We analyse the efficient sustainable equilibrium. Unlike in the standard economy, temporary economic shocks generate volatile and persistent changes in taxes along the equilibrium path. This serves to optimally limit rent-seeking by the politician and to optimally generate support for the politician from the citizens. Taxes resembling those of the benevolent government are very costly since the government over-saves and resources are wasted on rents. Political distortions thus cause the complete debt market to behave as if it were incomplete. However, in contrast to an incomplete market economy, in the long run, taxes do not converge to zero, and under some conditions, they resemble taxes under a benevolent government.